Role of DAZgene microdeletionandAMH changesin Azoospermia and Oligozoospermia patients - Kadhim, Noor Kareem; Zghair, Khawla Hori; Fakhrildin , Muhammad-Baqir (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to detect the microdeletions ofDAZin azoospermic and oligozoospermic patients and assessment of anti-müllerian hormone (AMH). One hundred patients included in this study,amplification of PCR by specific primer sets. All the samples tested for the presence of STS markers sY254 to detect AZFcDAZ gene deletions.The processed DNA was subjected to monoplex PCR, each specific region of the AZF locusamplifies by primer pair. AMH hormone level measured by ELISA kit.microdeletion of DAZ found in 20 of samples, present in 10(50%) in azoospermic patients with decreased in AMH level and oligozoospermic patients had 7(35%) while 3(15%) in normozoospermic men.Based on results, this study has shown DAZ genes microdeletion and decrease in AMH level are a major causes of male infertilityin this study and this microdeletions were more incidences in azoospermia more than oligozoospermia.